A kemelized Probabilistic Neural network approach for counting pedestrians - Lim, Eng Aik; Zarita, Zainuddin (Institute of Electrical and Electronics Engineering (IEEE), 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/